Facebook Base Writing Learning For Teaching English As A Foreign Language - Alfian Cahyo Budiardi; Baity Anggraeni (Bandar Lampung University (UBL), 2013)
Technology is something which cannot be avoided in our daily lives. It reaches many sectors of life; one of them is education especially in teaching writing. Recently, many teachers are still use a conventional method and approach to teach their students. On the other hands, students are familiar with Facebook. They use it almost every day in their spare time. There a lot of menu on it that is usually used with its own function. So, it is important to create a new effective way in teaching by taking some advantages from the development of the technology especially Facebook.This Facebook Base Writing Learning is a new innovation in teaching writing in which the teacher uses Facebook as the media in teaching it. The teacher applies it in Facebook’s group where the members of the group are the students of writing class who are taught by the teacher. The students are asked to post their works in that group and having a peer evaluation in that group to make it better. Then, the teacher asks them to revise their works based on the comments given by their friends.In evaluating the students, the teacher is not only focus on the final result of the students’ works but also considering the students’ activities during in the classroom including the students’ participation and how the students’ develop their skills. Teacher also gives materials in the class.To apply this method and approach, teacher needs to make a group in Facebook and let their students join it. Then, students are playing their roles on this phase to develop their skills by having practices in the group which will be evaluated by peer evaluators with teacher’s guidance.